Differences in geochemical characteristics of produced water from coalbed methane wells and their indications for drainage：A case study of the Santang Syncline in Western Guizhou - Xiaozhi ZHOU; Shuaiqi WANG; Shiliang ZHU; Shaolei WANG; Gang XIANG; Xuehua CHEN; Jihang DONG; Xin QIU (Meitan kexue jishu)
The produced water from coalbed methane (CBM) wells contains abundant geological information. Analyzing its geochemical characteristics and inter-well differences can provide scientific guidance for fine-scale drainage. Taking the Santang Syncline of the Zhijin-Nayong Coalfield in Western Guizhou as the study area, this paper explores the differences in geochemical characteristics, the genesis of the produced water from CBM wells, and the fine drainage control strategies under the background of complex structures. Based on the regular sampling and testing of the produced water from three CBM wells, the differences in water production, water quality, hydrochemistry, and hydrogen and oxygen isotopes in the water are analyzed. The water production patterns of CBM wells and the coordinated geological-engineering control effects on the differences between wells are discussed. The refined overflow release and drainage control measures after fracturing are proposed, which have guiding significance for the drainage work of CBM wells in complex structural areas. The research shows that the water production characteristics of CBM wells in the study area vary significantly between wells. Based on the identification of hydrogen and oxygen isotopes in water, Cl− concentration, pH value, etc., the produced water of Well W1, Well E1, and Well N1 mainly comes from the recharge of coal measure stagnant water, the recharge of overlying aquifer water, and the backflow of previously injected fracturing fluid, respectively. Affected by this, the trends of water quality changes of the produced water during the overflow release and drainage processes after fracturing of CBM wells are different, the concentrations of anions and cations in water and the hydrochemical types are different, and the drift trends of hydrogen and oxygen isotopes are also different. Combined with the monitoring of the water quality and hydrochemical characteristics of the produced water from CBM wells, the overflow release process after fracturing is divided into four stages: trial flowback, constant-rate flowback, slow increase of the flowback rate, and rapid decrease of the flowback rate. The early drainage and production process is divided into five stages: trial pumping, pressure-controlled fluid drainage, slow pressure reduction, pressure-controlled gas production, and pressure reduction for production increase. For CBM wells with different sources of produced water, the basic principles of drainage control are determined by comprehensively considering the permeability of the coal reservoir and the intensity of external water recharge. For example, low-yield water wells with weak formation water recharge should be drained and produced with a high casing pressure and a low daily decline rate of the flowing pressure, while high-yield water wells with strong formation water recharge should be drained and produced with a low casing pressure and a high daily decline rate of the flowing pressure, so as to ensure the continuous and stable production of gas and water during the pressure reduction and production increase stage of CBM wells and continuously carry out low-concentration coal powder during the long-term drainage process.